2019
DOI: 10.1097/tin.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Demographics, Education, and Stress on Body Mass Index Among Jordanian University Students

Abstract: Obesity prevalence increased dramatically and impacted negatively on developing chronic diseases. The main objective of this study is to examine the association between body mass index (BMI) and demographic factors, stress, dietary intakes, and physical activity levels among Jordanian university students. A convenience sample was chosen from 3 universities. Data were analyzed based on questionnaires about BMI, dietary intakes, and demographics. The χ2 and Kruskal-Wallis tests were used to examine the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In our sample, overweight and obesity percentages were lower than in a previous study conducted on university students in Jordan. However, Amr et al reported that more males were overweight and obese than females (59), which was consistent with our findings as females were five times more likely to be classified as normal or underweight when compared to males. These findings might be related to an increase in the fear of weight gain among our female subjects (60).…”
Section: Discussionsupporting
confidence: 93%
“…In our sample, overweight and obesity percentages were lower than in a previous study conducted on university students in Jordan. However, Amr et al reported that more males were overweight and obese than females (59), which was consistent with our findings as females were five times more likely to be classified as normal or underweight when compared to males. These findings might be related to an increase in the fear of weight gain among our female subjects (60).…”
Section: Discussionsupporting
confidence: 93%
“…likely to have BMI ≥ 25 with an adjusted odds ratio 1.25 (0.71 -2.17) (Table 4). This was nearly similar to the study of impact of demographics, education, and stress on body mass index among Jordanian university students, that detected a higher percentage of overweight and obesity among fourth year students than first year (11) . On the other hand, A significant percentage of university freshmen students in USA were overweight or obese (9) .…”
Section: Discussionsupporting
confidence: 87%
“…These include age, ethnicity or national origin, socioeconomic status, marital status, and physical activity (Amr et al, 2018;Hedley et al, 2004;Simon et al, 2006). In addition, psychological stress is by itself a risk factor for obesity (Amr et al, 2019). Obesity is associated with many mood disorders (Lee and Nieman, 2012;Stunkard et al, 2003).…”
Section: Introductionmentioning
confidence: 99%